Moon of Treason - McDowell, Robert Emmett, 1914-1975; Mayan, Earl, 1916-2009 (Salt Lake City, UT : Project Gutenberg, 2021)
"Moon of Treason" by Robert Emmett McDowell is a science fiction novel written during the early 1950s. The story revolves around Clyde Vickers, a mutant who has been branded an outlaw and is struggling to navigate society that fears and despises him due to his differences. The book delves into themes of identity, societal acceptance, and the existential challenges faced by those deemed "other." The narrative follows Clyde Vickers as he tries to reclaim his freedom after being released from prison on Jupiter. Upon arriving back on the moon, he is quickly caught in a conspiracy involving an impersonation of himself, espionage, and a mission to rescue a kidnapped scientist. Throughout this adventure, Vickers uses his unique vision, which enables him to see matter in an unusual way, to outmaneuver both the International Spy Ring and the authorities that seek to exploit or eliminate him. As he confronts villains and navigates alliances, Vickers ultimately discovers a new sense of belonging when he finds acceptance among the very spies who initially sought to use him for their own gains. The book raises questions about morality, the nature of power, and what it means to be human in a world where societal norms dictate worth. (This is an automatically generated summary.)
Release date is 2021-03-04
Greg Weeks, Mary Meehan and the Online Distributed Proofreading Team at http://www.pgdp.net
Keywords: Science fiction; Adventure stories; Spy stories; Moon -- Fiction; Ex-convicts -- Fiction; Psychic ability -- Fiction